La Niña y los niños : effects of an unexpected winter on early life human capital and family responses (2015)
The text has three core themes. In the first chapter a scheme of the original exposure of Marx, which is relatively sparse in his work, is presented. Initially we outline his general notions, and then, the different forms of manifestation of this category: Differential Rent Type I and Type II, Absolute Rent and Monopoly Rent. In the second chapter the main notes and objections that have been made to the original presentation, mainly in Latin American and French literature, are discussed. These objections are examined, their scope is evaluated, and is analyzed what could be the origin of the mismatches identified, when judged that they are justified. A reformulation of the original approach to absorb or overcome these difficulties is proposed. Three cores of discussion are analyzed: the Marx notion of Absolute Rent and its connection to an organic composition of capital in agriculture abnormally low; the presentation of Differential Rent Type II and the relationship with an unequal distribution of agricultural capital; the difference in nature that Marx proposes between Differential  and Absolute Rent and the relationships established between the latter category with the private ownership of land. The chapter concludes with an outline of a general reformulation of the Marxist category of Rent, in order to overcome these criticisms and enhance its potential to interpret the dynamics of price formation and the distribution of value in capitalism. The latter is developed in the light of contemporary discussion of the Marxist theory of value, roughly following the perspective known as "New Approach".